Pathologists as Clinicians! - Haque, Anwar Ul (International Journal of Pathology, 2019)
Modern day management of patients is a multi-disciplinary team (MDT) job and pathologist is an important member of the team. However, there are gross misconceptions about the role of pathology and pathologists in patient management. Perception about role of pathologist varies indifferent societies. While in scientifically developed countries misconceptions are not that great, in underdeveloped countries there exist serious misconceptions. Some even think pathologists are not real physicians! Some consider that pathologists are confined to do the autopsies; whatever they do is too little and too late. Even regulatory authorities like Pakistan Medical & Dental Council (PMDC) has bracketed discipline of Pathology into basic sciences in contrast to radiology which is regarded a clinical discipline! The fact is that pathology is equal if not more clinical subject than radiology. Pathologists render specific diagnoses of the diseases than radiologists whose diagnoses often require pathological confirmation. An eminent pathologist described this difference aptly as “While radiology is study of shadows, pathology is study of substance”! We have no objection on radiology being included in clinical subject, but pathology must also be classified as clinical subject which indeed it is.